2t-5=7+t

Simple and best practice solution for 2t-5=7+t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2t-5=7+t equation:


Simplifying
2t + -5 = 7 + t

Reorder the terms:
-5 + 2t = 7 + t

Solving
-5 + 2t = 7 + t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1t' to each side of the equation.
-5 + 2t + -1t = 7 + t + -1t

Combine like terms: 2t + -1t = 1t
-5 + 1t = 7 + t + -1t

Combine like terms: t + -1t = 0
-5 + 1t = 7 + 0
-5 + 1t = 7

Add '5' to each side of the equation.
-5 + 5 + 1t = 7 + 5

Combine like terms: -5 + 5 = 0
0 + 1t = 7 + 5
1t = 7 + 5

Combine like terms: 7 + 5 = 12
1t = 12

Divide each side by '1'.
t = 12

Simplifying
t = 12

See similar equations:

| 3x+6x+18=180 | | 25m=500 | | 22x=4x+1 | | 10+5y=18 | | 3x-y+2z=20 | | 3(3r-6)-4(r-5)= | | 10+4n=82 | | 5/11-3/7 | | 186=46-u | | 6!/6 | | -2x+4=-x^2 | | .004(8-k)+.04(k-7)=1 | | 1000+200m=1500+1175m | | 15y-15=180 | | 5L-10=15 | | -0.1x+1.39=-0.3x+0.79 | | -18=-3(a+3)+12 | | 6t+5=2t+9 | | 4a+8b+4c=1 | | 15u+5=60 | | 48/2-4 | | x(x-8)+17=0 | | 4v+6=2v | | 1/5y-4=-3 | | 12x+13y=74 | | 40=5f+10 | | x*0.8=250 | | 21=e+18 | | 12x+137=74 | | 1/5y-4-3 | | 4t=3t+10 | | 5x+33y=58 |

Equations solver categories